Cost and Benefit of Revenge: A Sociology of Literature Study on Sidney Sheldon’s Master of the Game - Hasna Nurain Mukhsin (Journal of English Language Teaching, Linguistics, and Literature Studies, 2022)
Cost and Benefit of Revenge: A Sociology of Literature Study on Sidney Sheldon’s Master of the Game. Revenge as old as the existence of organism in the earth. Revenge occurs as the act of getting even or to punish the wrongdoer. This study aims to reveal the particular issue regarding revenge as it written down in the novel Master of the Game by Sidney Sheldon. This study utilized the theory sociology of literature by Alan Swingewood. This study used descriptive qualitative method to unravel the impact if revenge toward the characters. This study showed that each characters undergone different acts of revenge based on the three types of revenge and it also revealed that the revenge cost more that benefitted the characters.Keywords: cost, benefit, revenge